Interreligious Dialogue and The Problem of Truth Claims - Mohammad Hasan Basri (Al-Ulum, 2011)
This article explores why the truth claims emerge and become a serious problem among religions, and how to handle it next to build inter-religious dialogue, especially in the era of pluralism. He tried to examine the issue of truth claims and how to solve them within the framework of dialogue. This paper is intended to implement concrete steps to overcome the problem of truth claims among religions and strive for mutual understanding to build a pluralistic view of interreligious dialogue in the frame. To overcome the problem of truth claims in religion dialogue, there are three steps that can be done: first, an exclusive view. Both views, inclusive. The final step is a pluralistic outlook.